12. Clinical evaluation of a transmission detector system and comparison with a homogeneous 3D phantom dosimeter. (December 2018) - Giglioli, F.R.; Gallio, E.; Franco, P.; Badellino, S.; Ricardi, U.; Fiandra, C.
Abstract : Purpose: To evaluate the clinical performance of a novel detector based on transmission measurements. Methods: Fifty patients were included in the study. The treatment plans were generated by two different Treatment Planning Systems (TPS). All treatment plans were verified by the Dolphin and the Delta4 in the same session and then by the Delta4 alone. The attenuation factor was evaluated for each patient by comparing Delta4 measurements with and without Dolphin. Gamma evaluation was performed with both systems in order to compare the plan dose with the irradiated dose. Parameters of dose-volume based indices for PTV (Gamma index 2%-2 mm) and OARs doses (Dmax and dose at the threshold volume) were considered for Compass calculation and Dolphin reconstruction. Clinical decisions were made by two physicians in order to evaluate the "pass", "fail" or "evaluate" grade of the treatment plans. A statistical analysis was performed in order to find correlation among dose parameters and clinical evaluation. Results: A value of 10.7 ± 0.7 was found for detector attenuation. Both detectors showed high reproducibility and correlation between the 2 mm leaf errors and gamma metric, with Dolphin using 2%-2 mm and Delta4 only using 1%-1 mm. No patients were classified as "fail" by the two instruments as well as by physicians (Table 1 ); while no correlation was found between the Delta4 gamma metric and physician classification, a significant correlation was observed for Dolphin (Fig. 1). Conclusions: Our data have shown a correlation between clinical decision and PTV gamma metric in the PTV area for Dolphin system while no correlation was observed with Delta4 measurements; therefore the PTV number of points with gamma ⩾1 (2%-2 mm) seems to predict the consistency of the irradiated dose to the patient.